Differentiated perceived match load and its variability according to playing position in professional soccer players during an entire season - Azcárate, U.; Yanci, J.; Los Arcos, A. (Kinesiology, 2020)
The aims were to assess differentiated perceived match exertion and its variability according to playing psition for professional soccer players. Nineteen Spanish players declared their respiratory and muscular perceived exertions (PEs) after official matches during an entire season. Players were classified according to their playing position. In order to assess differentiated perceived match exertion, soccer players were asked to assess their perceived level of exertion following each official match. Considerable differences (p<.05; ES=.41 to 2.49) were found between some playing positions but not always in both dimensions of PE (respiratory and muscular). Advanced midfielders (AvMs), wide midfielders (WMs) and wing backs (WnBs) reported the highest match respiratory PE and muscular PE scores. Furthermore, match-to-match differentiated perceived match exertion variability ranged from 12.8 to 27.7% for respiratory perceived exertion and from 11.5 to 25.2% for muscular perceived exertion according to playing position. Match respiratory-muscular PE differences varied among the playing positions, showing higher muscular PE than respiratory PE in central backs (CBs), WMs and central midfielders (CMs) (p<.05; ES=-.35 to .68), but higher respiratory PE than muscular PE in wing backs (p<.05; ES=-.35). Soccer differentiated perceived match exertion is different inter and intra some playing positions, showing large swings for match-to-match variability between playing positions. These facts confirm that the deconstruction of the overall PE provides a more accurate evaluation of the subjective match internal load in some playing positions.